PENGARUH PRAKTEK MANAJEMEN LABA DAN RASIO PROFITABILITAS TERHADAP PERINGKAT OBLIGASI DI PASAR KREDIT INDONESIA - Nuraisyah Nuraisyah (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2015)
Effect of Earnings Management and Corporate Profitability Ratios Against Ranked Bonds in the credit markets Indonesia. This study with the aim to (1) analyze the effect of earnings management on bond ratings, (2) analyze the effect of the ratio of profitability to bond ratings. This study uses quantitative data, ie the data 54 qualified financial reports from 18 companies sampled and data research company bond rating on Capital Market Information Center (PIPM) database Makassar and bond rating companies listed on the OTC-FIS Stock Indonesia Stock for the period 2009 to 2011. Of these at select analysis data used is multiple regression analysis. The results showed that: (1) earnings management and significant negative effect on bond ratings, (2) profitability ratios positive and significant effect on bond ratings. This means that the management company is expected to minimize earnings management and focus on improving profitability. because according to the results of the study found that earnings management will lead to lower bond ratings and higher profitability ratio that will increase the rating of bonds.